Eliciting willingness to pay for fairtrade products with information. (January 2021) - Ruggeri, Giordano; Corsi, Stefano; Nayga, Rodolfo M.
Highlights: Consumers value the white refined cane sugar as having the same price as the white refined beet sugar. Knowledge of Fairtrade by Italian consumers is very limited. Consumers are willing to pay a premium for Fairtrade certified white refined cane sugar. Information about Fairtrade increase consumers' willingness to pay for certified sugar. Information is more effective for those consumers who boycott firms due to environmental reasons. Abstract: Since its foundation, Fairtrade certification has successfully entered the mainstream market in most developed countries, and certified products can be found on the shelves of the most famous retailers. However, using labels to inform consumers about the ethical sustainability of products does not imply that they will read or use them at the time of purchase, and providing additional information has been identified as a viable method to increase the pool of buyers of certified products. Using Becker-Degroot-Marschak experimental auction and white refined cane sugar packs, we elicit the homegrown value that consumers in Milan (Italy) associate with Fairtrade certification, and we investigate the effect of providing additional information about Fairtrade on their willingness to pay. Our results show that consumers positively evaluate the presence of the certification on the products as they are willing to pay a premium for the certified products, and the premium increases when consumers are exposed to additional information regarding the Fairtrade system. Furthermore, combining the results of the auction with data collected through questionnaires, we analyze consumers' profiles concerning their attitude towards Fairtrade certification and response to information.